Pemberdayaan Kader Posyandu dalam Program Gerakan Amankan Kehamilan dan Persalinan (GEBRAK) dengan Mobile Application Family Center Maternity Care (FCMC) - Nicky Danur Jayanti; Senditya Indah Mayasari (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Efforts to accelerate the success of reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), especially those related to maternal health efforts, are increasing cross-sectoral partnerships as outlined in a high-risk pregnant women's mentoring activity by cadres carried out in Malang City known as the GEBRAK (Movement to Secure Pregnancy and Childbirth) program.